1979
DOI: 10.1115/1.3450956
|View full text |Cite
|
Sign up to set email alerts
|

Velocity Measurements in Two Natural Convection Air Flows Using a Laser Velocimeter

Abstract: Velocities in two laminar free convection air flow fields were measured using a laser velocimeter. Velocities were first measured in the boundary layer around a heated vertical flat plate and results compare within two percent of theoretical and previous experimental (streak photography) data. Second, velocities were measured throughout a two-dimensional triangular enclosure, which consisted of two isothermal side walls (one heated and one cooled), an insulated bottom, and glass end plates. Enclosure data are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
41
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 0 publications
1
41
0
Order By: Relevance
“…A comparison study is performed by Ridouane et al (2005) where the authors compare their numerical results produced for two different boundary conditions, (a) cold base and hot inclined walls (b) hot base and cold inclined walls with the experimental results obtained by Flack (1980;1979). A good agreement has been obtained between the numerical predictions and the experimental measurements of Nusselt number.…”
Section: Introductionmentioning
confidence: 57%
See 4 more Smart Citations
“…A comparison study is performed by Ridouane et al (2005) where the authors compare their numerical results produced for two different boundary conditions, (a) cold base and hot inclined walls (b) hot base and cold inclined walls with the experimental results obtained by Flack (1980;1979). A good agreement has been obtained between the numerical predictions and the experimental measurements of Nusselt number.…”
Section: Introductionmentioning
confidence: 57%
“…The author also reported the critical Rayleigh numbers of the transition from laminar to turbulent regimes. Kent (2009a) has also investigated the natural convection in an attic space for two different boundary conditions similar to Flack (1980;1979). The author observed that for top heating and bottom cooling case the flow is dominated by pure conduction and remains stable for higher Rayleigh numbers considered.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations